Nanoparticle separation with a miniaturized asymmetrical flow field-flow fractionation cartridge - Müller, David; Cattaneo, Stefano; Meier, Florian; Welz, Roland; deMello, Andrew J. (Frontiers in Chemistry, 2015)
Asymmetrical Flow Field-Flow Fractionation (AF4) is a separation technique applicable to particles over a wide size range. Despite the many advantages of AF4, its adoption in routine particle analysis is somewhat limited by the large footprint of currently available separation cartridges, extended analysis times and significant solvent consumption. To address these issues, we describe the fabrication and characterization of miniaturized AF4 cartridges. Key features of the scale-down platform include simplified cartridge and reagent handling, reduced analysis costs and higher throughput capacities. The separation performance of the miniaturized cartridge is assessed using certified gold and silver nanoparticle standards. Analysis of gold nanoparticle populations indicates shorter analysis times and increased sensitivity compared to conventional AF4 separation schemes. Moreover, nanoparticulate titanium dioxide populations exhibiting broad size distributions are analyzed in a rapid and efficient manner. Finally, the repeatability and reproducibility of the miniaturized platform are investigated with respect to analysis time and separation efficiency.